Identifying Psychosocial Variables That Predict Safer Sex Intentions in Adolescents and Young Adults - Brüll, Phil; Ruiter, Robert A. C.; Wiers, Reinout W.; Kok, Gerjo (Frontiers in Public Health, 2016)
Young people are especially vulnerable to sexually transmitted infections. The triad of deliberate and effective safer-sex behavior encompasses condom use, combined with additional information about a partner’s sexual health, and the kind of sex acts usually performed. To identify psychosocial predictors of young people’s intentions to have safer sex, as related to this triad we conducted an online study with 211 sexually active participants aged between 18 and 24 years. Predictors (i.e. perceived behavioural control, subjective norms and intention) taken from Fishbein and Ajzen’s Reasoned Action Approach (RAA), were combined with more distal variables (e.g. behavioral inhibition, sensation seeking, parental monitoring, and knowledge about sexually transmitted infections). Beyond the highly predictive power of RAA variables, additional variance was explained by the number of instances of unprotected sexual intercourse during the last twelve months and reasons for using barrier protection during first sexual intercourse. In particular, past condom nonuse behavior moderated perceived behavioral control related to intended condom use. Further, various distal variables showed significant univariate associations with intentions related to the three behaviors of interest. It may, therefore, be helpful to include measures of past behavior as well as certain additional distal variables in future safer-sex programs designed to promote health sustaining sexual behavior.